Modeling and sensitivity analysis study of the reduction of NO sub x by HNCO. [RAPRENOx process] - Brown, N. J.; Garay, J. (Lawrence Berkeley Laboratory, 1992)
A chemical mechanism for the reduction of NOsub x by HNCO has been constructed to allow for the modeling of NOsub x in exhausts typical of natural gas combustion (RAPRENOx process). The reduction was modeled assuming plug flow, and either isothermal combustion or constant pressure adiabatic combustion. Variables were initial concentrations of NO, NOsub 2, CO, CHsub 4, Hsub 2, and HNCO as well as initial temperatures. Exhaust residence time was nominally 1 s. Reduction was not achieved for prototypical natural gas exhaust'' for a reasonable residence time. Radical generation is crucial for reduction. Hsub 2 addition enhanced ignition and reduction. The final combustion temperature determines where NOsub x reduction ceases and NOsub x production increases. Reduction increases with HNCO, and breakthrough of NHsub 3 and HNCO increses as well. Nsub 2O production is due to NCO + NO, but the reduction of NO also occurs through reactions associated with the Thermal De-NOx chemistry. NHsub 3 production and reactions are important to the reduction of NO. Sensitivity analysis under easy ignition conditions indicated that the same reactions involving nitrogen species, NHsub 2 and NNH, important in De-NOx, are important when HNCO is used to reduce NOsub x. A real combustion exhaust would contain radicals, but it would be neither isothermal nor adiabatic, and heat release and loss would accompany the reduction process. Three-body recombination reactions are important and need further study.(DLC)